WAYS TO INCREASE THE MOTIVATION TO STUDY THE RUSSIAN LANGUAGE AND LITERATURE (Web of Teachers: Inderscience Research, 2025)
This article discusses effective ways to increase motivation to study the Russian language and literature. Particular attention is paid to the role of modern teaching methods, interactive technologies, creative tasks and a personality-oriented approach. The importance of involving students in the cultural and literary context, as well as the use of game and design methods, is emphasized. In conclusion, a conclusion is made that the need for a complex approach to form a sustainable interest in the subject.